The Russian exclave of Kaliningrad. Challenges and limits of its integration in the Baltic region - Yann Richard; Alexander Sebentsov; Maria Zotova (Cybergeo)
Mainly based on a field research carried out in 2012 by an international research group, this paper aims to understand why it seems so difficult for Kaliningrad to get fully integrated in the Baltic region, although the conditions for the development of cross-border cooperation (CBC) and regional integration exist. The relative isolation of Kaliningrad from the rest of the Baltic region is caused by its particular status as a subject of disagreement between Russia and the European Union and by institutional policy. But there are also purely local reasons for that situation. The weak integration of Kaliningrad in Baltic exchange networks is also caused by the persistence of adverse geopolitical orientations in the local populations and persistent stereotypes in the public opinion.